Validation of a population-based method to assess drug-induced alterations in the QT interval: a self-controlled crossover study - Iribarren, Carlos; Round, Alfred D.; Peng, Jonathan A.; Lu, Meng; Zaroff, Jonathan G.; Holve, Taylor J.; Prasad, Amit; Stang, Paul (Pharmacoepidemiology and drug safety, 2013)
ABSTRACT Purpose The purpose of this study was to ascertain, in the context of an integrated health care delivery system, the association between a comprehensive list of drugs known to have potential QT liability and QT prolongation or shortening. Methods By using a self‐controlled crossover study with 59 467 subjects, we ascertained intra‐individual change in log‐linear regression‐corrected QT (QTcreg) during the period between 1995 and mid‐2008 for 90 drugs while adjusting for age, gender, race/ethnicity, comorbid conditions, number of electrocardiograms (ECGs), and time between pre‐ECG and post‐ECG. The proportion of users of each drug‐developing incident long QT was also estimated. Results Two drugs (nicardipine and levalbuterol) had no statistically significant intra‐individual QTcreg shortening effects, 10 drugs had no statistically significant prolonging effect, and 78 (87%) of the drugs had statistically significant intra‐individual mean QTcreg lengthening effects, ranging from 7.6 ms for aripiprazole to 25.2 ms for amiodarone. Three drugs were associated with mean QTcreg prolongation of 20 ms or greater: amiodarone (antiarrhythmic), terfenadine (antihistaminic), and quinidine (antiarrhythmic); whereas 11 drugs were associated with mean QTcreg prolongation of 15 ms or greater but less than 20 ms: trimipramine (tricyclic antidepressant), clomipramine (tricyclic antidepressant), disopyramide (antiarrhythmic), chlorpromazine (antipsychotic), sotalol (beta blocker), itraconazole (antifungal), phenylpropanolamine (decongestant/anorectic), fenfluramine (appetite suppressant), midodrine (antihypotensive), digoxin (cardiac glycoside/antiarrhythmic), and procainamide (antiarrhythmic). Conclusions QT prolonging effects were common and varied in strength. Our results lend support to past Food and Drug Administration regulatory actions and support the role for ongoing surveillance of drug‐induced QT prolongation. Copyright © 2013 John Wiley & Sons, Ltd.